2008
DOI: 10.2174/138920008784220600
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Phenol and Catechol Metabolites of PCBs Modulate Catechol-Omethyltransferase Expression Via the Estrogen Receptor: Potential Contribution to Cancer Risk

Abstract: Commercial PCB mixtures have been shown to induce liver tumors in female rats and this effect has been attributed to the effects of PCBs on estrogen metabolism. Catechol metabolites of PCBs are potent inhibitors of COMT activity and are likely to contribute significantly to reduced clearance of genotoxic catechol metabolites of estrogen. The effect of PCB metabolites on COMT expression in cultured cells was investigated to explore potential mechanisms by which PCB exposure alters catechol estrogen clearance. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Other studies in workers exposed to the PCB have reported an increased incidence of liver tumors [185][186][187][188] . Some possible mechanisms by which PCB can cause cancer have been assumed: Reactive oxygen species (ROS) is produced through the enzymatic oxidation or autoxidation of PCB; PCB determines the increased expression of genes responsible for inflammation and apoptosis in the liver; and PCB has "toxic" effects on certain genes, such as the loss of part of a chromosome and chromosome breakage [189][190][191][192][193][194][195][196][197][198][199] . ROS are also able to reduce telomerase activity which can determine telomere shortening.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Other studies in workers exposed to the PCB have reported an increased incidence of liver tumors [185][186][187][188] . Some possible mechanisms by which PCB can cause cancer have been assumed: Reactive oxygen species (ROS) is produced through the enzymatic oxidation or autoxidation of PCB; PCB determines the increased expression of genes responsible for inflammation and apoptosis in the liver; and PCB has "toxic" effects on certain genes, such as the loss of part of a chromosome and chromosome breakage [189][190][191][192][193][194][195][196][197][198][199] . ROS are also able to reduce telomerase activity which can determine telomere shortening.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Yet estrogen downregulates human COMT transcription in a dose- and time-dependent manner (Ho et al, 2008; Jiang et al, 2003; Xie et al, 1999) and results in COMT enzymatic activity being 30% lower in women than men (Boudikova et al, 1990; Chen et al, 2004; Cohn and Axelrod, 1971). The story that being homozygous for Met at codon 158 of COMT confers a cognitive advantage is not true for women during the portion of their menstrual cycle when their estrogen levels are high.…”
Section: Consequences Of the Relative Dearth Of Dat And Hence Dependmentioning
confidence: 99%
“…For example, PCBs induce CYPs in the liver, which may redirect the metabolism of endogenous estrogen to more harmful estrogen catechols (Ho et al, 2008), or generate ROS that produce estrogen quinones .…”
Section: (A) Induction Of Xenobiotic Metabolismmentioning
confidence: 99%